Loss of control vs. risk reduction: decision factors for hiring non-family CFOs in family firms - Eva Lutz; Stephanie Schraml; Ann-Kristin Achleitner (Technische Universität München, Center for Entrepreneurial and Financial Studies (CEFS), 2010)
Objectives: We examine decision factors of family firm owners for hiring a non-family Chief Financial Officer (CFO). We explore the perceptions of family firm owners towards external managers by analyzing how their family-specific and company-specific goals relate to the employment of a non-family CFO. Furthermore, we analyze the consequences of hiring a non-family CFO on financial policies such as the use of strategic financial plans and initiatives to improve relationships with external capital providers. Prior work: Prior research has acknowledged that the attitude to external managers is a major concern for family firms because of potential problems due to a separation of ownership and management. However, it was shown that non-family CFOs positively influence the operational performance of privately-held family firms. Little knowledge exists to date to explicitly link the decision to hire an external CFO to the goals of family firm owners. Approach: Our study is based on a survey of 237 small- and medium-sized privately-held German family firms in 2007. We use logistic regression analysis to test our theory-driven hypotheses on the relationship between family-specific as well as company-specific goals of the family and the employment of a non-family CFO. Furthermore, we use OLS and logistic regression analysis to analyze hypotheses on how non-family CFOs influence financial policies. Results: The results suggest that family firm owners are reluctant to hire non-family CFOs because of agency type of problems. They decide against an external CFO when their goal of independence and control is high. Furthermore, they do not seem to trust external managers to act in accordance to their goal of enterprise value growth. However, they seem to realize that non-family CFOs are likely to decrease financial risk through the provision of additional capabilities. Non-family CFOs are shown to influence financial policies and, thereby, to bring in value creating resources. Implications: Family firm owners can use the results to understand the relevant factors they should consider when employing an external CFO. In particular, they should focus on establishing incentive structures for external managers to follow goals of the family. Candidates for non-family CFOs are able to better comprehend the underlying objectives of family firm owners in the hiring decision. Value: Our findings are relevant to further disentangle the relationship between external managers and family firm owners. By applying both the agency theory and the resource based view, we are able to offer explanations for and against the decision to hire non-family CFOs in family firms.
Keywords: G30; G32; L26; 330; CFO; family firms; financial policy; entrepreneurial finance; corporate governance; Betriebliche Finanzwirtschaft; Führungskräfte; Finanzvorstände; Führungskräfteauswahl; Entscheidung; Corporate Governance; Familienunternehmen